2017
DOI: 10.4269/ajtmh.16-0904
|View full text |Cite
|
Sign up to set email alerts
|

A New Handheld Device for the Detection of Falsified Medicines: Demonstration on Falsified Artemisinin-Based Therapies from the Field

Abstract: Poor-quality medicines are a major problem for health-care systems in resource-poor settings as identifying falsified medicines requires a complex laboratory infrastructure such as a Medicines Quality Control Laboratory. We report here an evaluation of a low-cost, handheld near-infrared spectrometer (NIRS) device by analyzing a library of artemisinin-based combination therapy (ACT) medicines to determine its usefulness as a drug-screening tool. The “SCiO” research prototype device was used to collect NIR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Symbiotic sources. In fact, 20 seeds were enough to have a 95% chance of appropriately assigning the category, thus confirming previous results 23 pertaining to the detection of falsified medicines. The instrument is also suitable for practical applications, as shown by its capacity to discriminate frozen milk samples originated from either grass-fed or from conventional fed cows 24 as well as to assess oxidative stress from a simple NIRtomoscopy of the ear of rabbit does 25 .…”
Section: Discussionsupporting
confidence: 87%
“…Symbiotic sources. In fact, 20 seeds were enough to have a 95% chance of appropriately assigning the category, thus confirming previous results 23 pertaining to the detection of falsified medicines. The instrument is also suitable for practical applications, as shown by its capacity to discriminate frozen milk samples originated from either grass-fed or from conventional fed cows 24 as well as to assess oxidative stress from a simple NIRtomoscopy of the ear of rabbit does 25 .…”
Section: Discussionsupporting
confidence: 87%
“…The device has been successfully proven able to discriminate mountain from plain dairy iced milk [34]. In the fight against commercial fraud, Wilson et al [35] found SCÏO to be useful for identifying authentic artemisinin-based compounds and suggested that it could enable widespread drug screening at multiple points in the health network. In a recent review, Kademi et al [36] discussed new NIRS devices that might stand as promising alternatives to large, expensive, benchtop types in food analysis, inspection, and control.…”
Section: Discussionmentioning
confidence: 99%
“…Even the poor countries are supposed to afford rapid detection tools in order to be able to identify these bad medicines in their supply chain and at the points of entry into their countries. The advent of a less expensive, hand-held near-infrared spectrometer (NIRS) as a portable device for the detection of quality assured and SFM of artemisinin-based combination therapy (ACT) medicines is important progress (31). NIRS, which cost only around US$1,000 has shown promising results for the screening of falsified ACTs samples from Equatorial Guinea and Ghana, and it can facilitate cheaper rapid testing at any country's point of entry and in the supply chain (31).…”
Section: Methods and Technologies For The Detection Of Substandard Anmentioning
confidence: 99%